2013
DOI: 10.1128/aem.01436-13
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Cell-to-Cell Signaling Does Not Abolish the Antagonism of Phaeobacter gallaeciensis toward the Fish Pathogen Vibrio anguillarum in Algal Systems

Abstract: Quorum sensing (QS) regulates Phaeobacter gallaeciensis antagonism in broth systems; however, we demonstrate here that QS is not important for antagonism in algal cultures. QS mutants reduced Vibrio anguillarum to the same extent as the wild type. Consequently, a combination of probiotic Phaeobacter and QS inhibitors is a feasible strategy for aquaculture disease control. Bacteria predominantly exist in mixed populations, and the behavior of the complete population is often affected by highly structured and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Berger et al. 2011; Prol García, D'Alvise and Gram 2013) could contribute to the higher maximal levels of TDA during growth with excess of nitrogen (Fig. S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Berger et al. 2011; Prol García, D'Alvise and Gram 2013) could contribute to the higher maximal levels of TDA during growth with excess of nitrogen (Fig. S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, it was found that null mutants of pgaI and pgaR cannot synthesize tropodithietic acid (TDA), an antibiotic produced by several members in the Roseobacter clade, and also fail to produce a yellow-brown pigment, when grown in marine broth with shaking for 24 h [ 26 ]. However, recent studies show that different carbon sources determine the role of QS in regulating the production of TDA [ 28 ] and the production is only delayed in QS mutants in agitated culture in marine broth [ 27 ]. More importantly, QS is not important for the TDA production when P. inhibens DSM17395 is used as a probiotic treatment in aquaculture system [ 27 ].…”
Section: Qs In Phaeobacter Inhibens Dsm17395mentioning
confidence: 99%
“…Phaeobacter and Ruegeria strains have repeatedly been isolated from aquaculture units and are harmless to fish larvae and their live feed (12)(13)(14)(15)(16). The probiotic (antibacterial) effects of Phaeobacter and Ruegeria are predominantly caused by their production of the dual-sulfur tropone-derived com-pound tropodithietic acid (TDA) (16)(17)(18)(19). TDA-producing Phaeobacter and Ruegeria strains can prevent vibriosis in cod larvae (16) and reduce mortality rates for turbot larvae (15) and Artemia (20) challenged with V. anguillarum and V. harveyi, respectively.…”
mentioning
confidence: 99%